Hypolipidemic Effect of Oral Administration of Aqueous Leaf Extract ofSenna occidentalisin Rats - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Senna occidentalisis a medicinal plant which is called “rai–rai” or “rai dorai” in Hausa. It is among the most commonly used plants that form the basis of primary healthcare for a majority of people living in rural and remote areas in Nigeria and other third world countries. Hyperlipidemia is a condition which is characterized by elevated levels of serum lipid profile. It is associated with many diseases such as atherosclerosis, cardiovascular diseases, and diabetes.Aims and Objectives:This study was aimed at assessing the effect of oral administration of aqueous leaf extract ofS. occidentalison serum lipid profile in rats.Materials and Methods:Phytochemical screening and effect of aqueous leaf extract ofS. occidentalison lipid profile was conducted. Thirty male albino rats were divided into six groups of 5 rats each. Group I was normal control, group II hyperlipidemic control, groups III, IV, and V were hyperlipidemic rats orally administered with 500 mg/kg, 250 mg/kg, and 166 mg/kg of aqueous leaf extract ofS. occidentalis, respectively, for 4 weeks, and group VI were hyperlipidemic rats orally administered with 10 mg/kg of ruvastatin for 4 weeks. At the end of the fourth week, the animals were sacrificed and their serum total cholesterol (TC), triglycerides (TG), high density lipoprotein (HDL), and low density lipoprotein (LDL) levels were determined.Results:Results of phytochemical screening revealed the presence of tannins, saponins, cardiac glycosides, resins, and flavonoids. Significant (P< 0.05) increase in the serum TC, TG, and LDL-chol were observed in groups II, III, IV, V, and VI when compared with that of the control rats. Significant (P< 0.05) decrease in mean serum TG, TC and LDL-chol levels were found in rats orally administered with 500 mg/kg of aqueous leaf extract ofS. occidentalisand those orally administered with 10 mg/kg of rosuvastatin when compared with group II. Rats orally administered with 250 mg/kg of the aqueous leaf extract were found to have significantly lower (P< 0.05) mean serum TC and LDL-chol when compared with that of group II (test control).Conclusion:It could be suggested that aqueous leaf extract ofS. occidentalisat 500 mg/kg could cause antihyperlipidemic effect against dietary-induced hyperlipidemia.